Creatine kinase and ATPase activities in piglets fed a fungal mycotoxin co-contaminated diet: Consequences in the pathogenesis of subclinical intoxication - Baldissera M.D. (2018)
© 2018 Elsevier LtdCreatine kinase (CK) activity, through the creatine-kinase-phosphocreatine (CK/PCr) system, provides a temporal and spatial energy buffer to maintain cellular energetic homeostasis, being responsible to provide adenosine triphosphate (ATP) to the proper function of ATPases enzymes, such as the sodium-potassium (Na+, K+-ATPase) and hydrogen (H+-ATPase) pumps. Thus, the aim of this study was to evaluate the involvement of CK/PCr system in the impairment of energetic homeostasis in piglets fed with a diet co-contaminated with mycotoxins, as well as the effects on ATPases enzymes. Animals were randomly divided in two groups (eight repetitions with two animals each): CON (basal diet) and MYC (mycotoxin diet; 9300 μg/kg of aflatoxins and 8000 μg/kg of fumonisins) which were feed during 15 days. Piglets that received a diet containing 300 μg/kg of aflatoxins and 8000 μg/kg of fumonisins (MYC group) presented lower body weight on days 10 and 15 of experiment when compared to control (CON group). Serum CK activity was lower on days 5, 10 and 15 of experiment in the MYC group. The same occurred for serum Na+, K+-ATPase and H+-ATPase activities on days 10 and 15 when compared to CON group. Moreover, serum calcium levels were superior on day 15 of experiment in the MYC group, while serum potassium and sodium levels were lower in comparison to CON group. Based on these evidences, a diet co-contaminated by aflatoxins and fumonisins inhibits serum CK activity, impairing the energetic homeostasis. This inhibition alters the activities of ATPases (Na+, K+-ATPase and H+-ATPase), contributing to the imbalance of Na+, K+ and Ca+ ionic levels. In summary, the cascade of alterations contributes directly to disease pathogenesis of piglets intoxicated by mycotoxins.